Compressor Surge and Rotating Stall Modeling and Control - Gravdahl, Jan Tommy; Egeland, Olav (Advances in Industrial Control, 1999)
This work gives a comprehensive overview of the achievements in the field of modeling and active control of instabilities in compressions systems over the last decade. Existing models of unstable compression systems are in most cases restricted to constant speed compressors. Here, two models are derived that take time varying rotational speed into account - one for centrifugal compressors and one for axial compressors. • The main focus of the modeling element is the inclusion of non-constant speed in existing dynamic models of unstable compression systems, and the study of surge and rotating stall in connection with this. • The focus of the control element is the use of a close coupled valve as a means of stabilising surge and rotating stall. Little work has yet been published on this. Using techniques such as backstepping and passivity, controllers for a close coupled valve in the compression system are derived in order to stabilise the compressors and extend the range of mass flows over which it can be operated stably. Detailed analysis of the closed loop systems is performed and many case studies with simulations are presented. Scientists and graduate students working in this area will find this particularly useful. It will also be a valuable addition to libraries and the industry as a whole. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control